MADU DALAM PERSPEKTIF AL-QUR'AN DAN SAINS MODERN: ANALISIS QS. AN-NAHL AYAT 68-69 DAN TEMUAN PETER MOLAN TENTANG MANFAAT TERAPIUTIK MADU - Isqi, Nabil; Nasikhin, Naskhin; Bisri, Kasan (IAINU Kebumen Prodi IAT, 2025)
Honey has long been recognized as a natural substance with therapeutic benefits, both in the Qur'anic perspective and modern medicine. This study aims to analyze the alignment between the Qur'anic view (QS. An-Nahl verses 68-69) of honey as a